A High Throughput Lipidomics Method Using Scheduled Multiple Reaction Monitoring - Akash Kumar Bhaskar; Salwa Naushin; Arjun Ray; Praveen Singh; Anurag Raj; Shalini Pradhan; Khushboo Adlakha; Towfida Jahan Siddiqua; Dipankar Malakar; Debasis Dash; Shantanu Sengupta (Biomolecules, 2022)
Lipid compositions of cells, tissues, and bio-fluids are complex, with varying concentrations and structural diversity making their identification challenging. Newer methods for comprehensive analysis of lipids are thus necessary. Herein, we propose a targeted-mass spectrometry based lipidomics screening method using a combination of variable retention time window and relative dwell time weightage. Using this method, we identified more than 1000 lipid species within 24-min. The limit of detection varied from the femtomolar to the nanomolar range. About 883 lipid species were detected with a coefficient of variance <30%. We used this method to identify plasma lipids altered due to vitamin B12 deficiency and found a total of 18 lipid species to be altered. Some of the lipid species with ω-6 fatty acid chains were found to be significantly increased while ω-3 decreased in vitamin B12 deficient samples. This method enables rapid screening of a large number of lipid species in a single experiment and would substantially advance our understanding of the role of lipids in biological processes.